2013
DOI: 10.1007/s00246-013-0704-6
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin A1c in Pregestational Diabetic Gravidas and the Risk of Congenital Heart Disease in the Fetus

Abstract: This study aimed to determine whether poor glycemic control in early pregnancy is associated with an increased risk of congenital heart disease (CHD) for infants of women with preexisting diabetes. A retrospective review examined two tertiary care centers of diabetic pregnancies that recorded early hemoglobin A1c (HbA1c) values (<20 weeks). The incidence of prenatally diagnosed CHD was calculated and stratified by HbA1c level. Poor glycemic control was defined as an HbA1c level of 8.5 % or higher. Fetal echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…1214 Some studies suggest that the excess risk can be eliminated with optimal diabetes management prior to and during early pregnancy. 8,13,1517 …”
Section: Introductionmentioning
confidence: 99%
“…1214 Some studies suggest that the excess risk can be eliminated with optimal diabetes management prior to and during early pregnancy. 8,13,1517 …”
Section: Introductionmentioning
confidence: 99%
“…The most common cardiac anomalies are conotruncals and defects of the interventricular septum [10]. Usually they are presented in a moderate, asymptomatic and transient form, however, congestive cardiomyopathy may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Usually they are presented in a moderate, asymptomatic and transient form, however, congestive cardiomyopathy may occur. These changes appear more frequently in fetuses of pregnant women with poor metabolic control [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, hyperglycemia is considered to be a primary teratogen affecting organ development. Some retrospective reviews of diabetic pregnancies in human reported that poor glycemic control in early pregnancy is associated with increased risk of heart defects in offspring; the incidence of CHD in PGDM patients with a level of hemoglobin A1c (HbA1c) above 8.5% was almost three times higher than the incidence observed in patient with HbA1c levels lower than 8.5% [6,7]. Furthermore, fetal glucose concentration depends on fetal glucose uptake.…”
Section: Introductionmentioning
confidence: 99%